Pre‐Graduation Transition Services for Improving Employment Outcomes among Persons with Autism Spectrum Disorders: A Systematic Review - John D. Westbrook; Carlton J. Fong; Chad Nye; Ann Williams; Oliver Wendt; Tara Cortopassi (Campbell Systematic Reviews, 2013)
The objective of this Campbell systematic review was to determine the effectiveness of pre‐graduation interventions aimed at persons with autism spectrum disorders (‘ASD’) to shape behaviors, social interactions, and/or skills that result in employment in mainstream competitive employment settings. No studies were identified that met all the inclusion criteria specified for the review. This review was not able to identify definitive interventions that predictably and positively supported the development of transition programs designed to produce employment outcomes for individuals with ASD. Given the regulations and funding often surrounding transition programming for students with disabilities, it is remarkable that such limited research attention has been paid to the effectiveness of interventions that produce the intended result of such programs. Future research efforts are needed to develop studies that utilize a rigorous experimental design to determine the relative effectiveness of the various interventions being utilized in transition programming for students with ASD. It is also important for such studies to identify actual employment outcomes that result from presumed preparatory or facilitating interventions utilized in transition programs. Executive Summary/Abstract BACKGROUND As the number of individuals diagnosed with autism spectrum disorders (ASD) rises, attention is increasingly focused on potential employment outcomes for individuals with ASD, especially for those individuals that are exiting public school settings. Individuals without disabilities are eight times more likely to be employed than individuals with severe disabilities (National Organization on Disability, 2000). Individuals with ASD are among those least likely to be employed (Cameto, Marder, Wagner, & Cardoso, 2003; Dew & Alan, 2007). Although economic conditions and employer attitudes are important factors in acquiring employment opportunities for individuals with ASD, appropriately addressing specific behaviors common among individuals with ASD can greatly improve employment outcomes (Schaller & Yang, 2005). OBJECTIVE To determine the effectiveness of pre‐graduation interventions aimed at persons with autism spectrum disorders to shape behaviors, social interactions, and/or skills that result in employment in mainstream competitive employment settings. SEARCH STRATEGY Studies were identified using electronic search techniques of 30 computerized databases. The keywords used in the computerized bibliography searches were divided into three categories: population, treatment, and domain and design characteristics. The searches covered the period from 1943 through 2011. Grey literature identified through electronic searches was submitted to the same inclusion criteria as other studies. The same time range (1943 ‐ 2011) and inclusion criteria were applied to a search of the grey literature for unpublished studies. References from individual studies were searched for potential studies to consider for inclusion. In addition, unpublished dissertations and theses were identified through the search strategy for review and consideration. SELECTION CRITERIA A two‐stage process was used to determine inclusion or exclusion of studies: (1) title and abstract stage and (2) full text stage. The participant sample of the study was secondary school‐age individuals (ages 14‐22), with a diagnosis of Autism Spectrum Disorder (ASD). Interventions for this review were included if they were designed as an approach to prepare and/or place transition‐age individuals with ASD into gainful employment. Interventions that address the acquisition of job‐related skills/behaviors or social employment‐appropriate skills/behaviors without an employment outcome were excluded. Studies with a research design of randomized controlled trials, quasi‐experimental, or single subject experimental were coded for inclusion. DATA COLLECTION AND ANALYSIS The combined electronic and hand searches produced a total of 5,665 citations at Stage 1 Title/Abstract. Of these studies a total of 85 citations were advanced for collection of a full text copy of the study (Full‐Text Stage 2). The search results were examined independently by three of the review authors. RESULTS This review was not able to identify definitive interventions that predictably and positively supported the development of transition programs designed to produce employment outcomes for individuals with ASD. Upon review of the full‐text for each of the 85 studies, no studies were identified that met all the inclusion criteria specified for the review. The following describes the reasons for exclusion of the studies identified through the Stage 2 review procedures: studies that did not describe or assess an intervention (n = 40), did not present outcomes related with gainful employment (n = 38), did not contain participants with ASD (n = 3), or did not provide quantitative data (case study) (n = 4). AUTHORS' CONCLUSIONS While no definitive conclusions can be drawn based upon the current review, the authors did identify qualitative research and other related studies that addressed elements of potential successful employment placements for transition‐age individuals with ASD that are detailed in Appendix B. Given the regulations and funding often surrounding transition programming for students with disabilities, it is remarkable that such limited research attention has been paid to the effectiveness of interventions that produce the intended result of such programs. Future research efforts are needed to develop studies that utilize a rigorous experimental design to determine the relative effectiveness of the various interventions being utilized in transition programming for students with ASD. It is also important for such studies to identify actual employment outcomes that result from presumed preparatory or facilitating interventions utilized in transition programs.